Economic development in Ghana and Malaysia: A comparative analysis - Andoh, S.K.; de Gannes Scott, B.J.; Ofori-Abebrese, G. (Economic Development in Ghana and Malaysia: A Comparative Analysis, 2020)
Economic Development in Ghana and Malaysia investigates why two countries that appeared to be at more or less the same stage of economic development at one point in time have diverged so substantially. At the time of their independence from the UK in 1957, both Ghana and Malaysia were at roughly the same stage of economic development; in fact, Ghana's real per capita income was slightly ahead of Malaysia's. Since then, Ghana's development has been sluggish, while Malaysia's economy has taken off into sustained growth and today, the real per capita income of Malaysia is about five times that of Ghana. This volume examines the pre-colonial and colonial economies of both countries, and the economic policies pursued after independence. In doing so, it aims to identify policies which might have contributed to Malaysia's development and those which might have slowed Ghana's. The authors ask whether lessons can be learned from the successes of countries such as Malaysia. This detailed comparative analysis will be useful to students and researchers of development economics as well as public policy makers in developing countries. It is written in language which makes it accessible to the general reader. © 2020 Samuel K. Andoh, Bernice J. deGannes Scott and Grace Ofori-Abebrese. All rights reserved.
Keywords: dept.eco; peer-reviewed

No more nursing homes? Changes in consumer preferences for long-term care facilities following COVID-19 - Schultz, Amber F; Yu, Jia (British Journal of Healthcare Management, 2020)
Since the first COVID-19 case was discovered in December 2019, over 12.1 million cases have been reported in more than 188 countries and territories. In the USA, the Centers for Disease Control and Prevention has confirmed almost 3.05 million COVID-19 cases, with more than 132 000 deaths. The COVID-19 pandemic has had a particularly dramatic impact on the elderly and those with chronic underlying medical disorders. Before the second outbreak in July, long-term care facilities were the most severely affected in terms of case numbers, especially nursing homes. This article provides information and insight into the potential changes in consumer preferences toward long-term care facility selection and the possible structural change of the long-term care industry in three aspects; structure, conduct and performance. © 2020 MA Healthcare Ltd. All rights reserved.
Keywords: Covid-19; Home care service; Long-term care facility; Nursing home; dept.eco; peer-reviewed

Genetically modified crops’ environmental impact and trust in eco-labels - Kwak, Lynn E.; Yoon, Sang Won; Kim, Younjun (Australasian Marketing Journal, 2020)
The U.S. Department of Agriculture expects companies to disclose genetically modified (GM) ingredients in foods and beverages by January 2022. While food companies fear that the stigma of GM labels could cause GM food sales to decline, eco-labeling could lessen the impact of GM-labeling. The results of the present research indicate that neither the eco-labeling alone nor the eco-labeling accompanied by information about the environmental benefits of GM crops influence consumers’ willingness to buy. Based on the mediation analysis, however, trust of eco-labels mediates the relationship between GM foods’ environmental friendliness information and consumers’ willingness to buy eco-labeled GM food. The theoretical and practical implications of the findings are discussed. © 2020
Keywords: Eco-labeling; Genetically modified (GM) foods; Trust; Willingness to buy; dept.eco; dept.mkt; peer-reviewed

‘Is it wise to open up America again now?’ Learning from government responses to COVID-19 and economy reopen points in three Asia-Pacific countries - Yu, Jia; Pang, Yulei (British Journal of Healthcare Management, 2020)
With the continuously increasing number of new confirmed COVID-19 cases, many health experts worried about the possibility of a ‘second wave’ outbreak, which might cause more deaths and hit economies even worse. This article looks at the experiences of fighting COVID-19 from three Asia-Pacific countries and discusses whether it is a wise decision to open up America again at this time.
Keywords: dept.eco; dept.mat; peer-reviewed

Sustainable development: Structural transformation and the consumer demand - López, Ramón E.; Yoon, Sang W. (Structural Change and Economic Dynamics, 2020)
This paper examines the feasibility of environmentally sustainable growth in a competitive market economy assuming various types of technological changes affecting pollution emissions and ultimately climate change. We consider two final outputs and two factors of production, accounting for both pollution flow and stock effects. If the initial level of pollution emissions satisfies certain boundary conditions, a Pigouvian pollution tax may assure sustainable growth without any further government intervention. This is true even if exogenous technological change is assumed to benefit exclusively the pollution-intensive industries (the “dirty” sector). A consumers’ composition effect (often neglected in the literature), driven by an endogenous change in the relative prices between clean and dirty final goods under an optimal pollution tax, plays a critical role in the structural transformation process to achieve long-run sustainable economic growth.
Keywords: Consumption flexibility; Optimal pollution tax; Sustainable development; Technological change; boundary condition; dept.eco; economic growth; emission; environmental economics; pollution tax; sustainable development; technological change

ICT and transport infrastructure development: an empirical analysis of complementarity - Na, Kyoung Y.; Kim, Dong H.; Park, Byoung G.; Yoon, Sang W.; Yoon, Chang-Ho (Applied Economics, 2020)
This paper provides an empirical framework to assess the nonlinear complementary linkage effects that arise from the interaction between motorway capital and information and communications technology (ICT) capital in developed economies. Using panel data from the Organisation for Economic Co-operation and Development (OECD) member countries and controlling for endogeneity, the paper finds that there exists a critical mass for ICT capital such that if the capital grows beyond the critical mass, the marginal contribution of motorway capital to productivity growth increases as the motorway is extended. This empirical result explains variations in the productivity contributions of transport infrastructure across countries that differ in their ICT infrastructure and has implications for setting the investment priorities of key components of infrastructure. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: ICT capital; OECD; complementarity; dept.eco; empirical analysis; information and communication technology; infrastructural development; infrastructure development; motorway; panel data; peer-reviewed; productivity; productivity growth; transportation infrastructure

The intra-industry effects of proxy contests - Chen, Fang; Huang, Jian; Yu, Han (Journal of Economics and Finance, 2020)
In this study, we examine the intra-industry effect of proxy contests. Proxy contests convey the information of common industrial risks or expected competitive relationship change. We find significant negative abnormal returns in the group of competitors of target firms with negative abnormal returns, and such negative abnormal returns become larger for similar-size competitors. In contrast, there are no significant abnormal returns for competitors of target firms with positive abnormal returns. These findings are consistent with the information-based theory but not the competitive theory. © 2019, Academy of Economics and Finance.
Keywords: Competitive effect; Information-based effect; Intra-industry effect; Proxy contest; dept.eco; dept.fin; peer-reviewed